Pengaruh Ukuran Dewan Direksi Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Moderating Variabel - Cindy Carolina; Vina Vernnita; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This research aims to examine whether there is a relationship between board of director’s size with firm value and whether firm size also influences the relationship. This research also uses managerial ownership and profitability as control variables. The object of this research are 92 manufacturing companies which listed on Indonesia Stock Exchange in 2015-2019 which were selected by purposive sampling method. The research hypothesis was tested using a panel data regression model which was processed using GRETL software. Based on the results of the analysis, it is found that firm size strengthens the relationship between bord of director’s size with firm value.